Gunnar Myrdal on Labour Market Regulation and Economic Development - Guglielmo Forges Davanzati (Œconomia, 2013)
This article proposes a re-reading of Gunnar Myrdal’s theory of the functioning of the labour market. In contrast with the conventional view of his time (what he labelled “equilibrium economics”), Myrdal upholds that a deregulated market economy is unable to spontaneously generate a social environment characterized by “harmony of interests”. In this context, income inequality perpetuates both within countries and between countries. For the purpose of obtaining a more equal income distribution—and higher economic growth—, an external intervention is necessary, by means of the creation and the progressive expansion of the Welfare State. More peculiarly, it will be shown that for Myrdal economic growth is driven by labour market regulation, increasing public transfers to the benefit of workers and the payment of unemployment benefits, in a theoretical schema where aggregate demand and aggregate supply systematically interact according to a cumulative process.